The Role of Magnesium Supplementation for Supportive Therapy in Covid-19 Infection - Solikhah, Amanatus; Ihsana, Nuni; Sofro, Abdul Salam (Ahmad Dahlan Medical Journal, 2021)
The coronavirus disease 19 (COVID-19) caused by SARS-CoV-2 created global pandemic conditions. A person infected with SARS-CoV-2 increases the probability of hospitalization and admission to intensive care, with high mortality. The most common symptoms of COVID-19 patients are fever and cough, although a variety of other symptoms may also be present. Patients admitted to the intensive care unit are known to have impaired organ function including acute respiratory distress syndrome (ARDS), cardiac injury, acute kidney injury, and liver dysfunction. Increasing evidence supports that magnesium supplementation (especially magnesium sulfate and magnesium oxide) prevents or treat various types of disorders or diseases related to the respiratory system, reproductive system, nervous system, digestive system, cardiovascular system, kidney injury, diabetes and cancer.